Epigenetic regulation in spinal muscular atrophy: emerging areas and future directions - Haoran Li; Bo Yu; Ye yuan; Nannan Chen; Jimeng Wu; Zhiqing Zhang (Orphanet Journal of Rare Diseases)
Abstract Spinal Muscular Atrophy (SMA) is a neuromuscular disorder precipitated by mutations or deletions in the Survival Motor Neuron 1 (SMN1) gene. Although the SMN2 gene partially compensates for SMN1 functional deficiency, its expression is regulated by complex epigenetic and environmental factors. This review comprehensively elucidates the regulatory mechanisms through which epigenetic modifications-encompassing DNA methylation, histone modifications, and non-coding RNAs-modulate SMN2 gene expression and impact SMA pathogenesis and progression. We also briefly discuss how these epigenetic mechanisms may interact with selected environmental factors in modifying disease outcomes. Emerging evidence suggests that these epigenetic factors and environmental exposures interact synergistically to influence disease trajectory and may account for the heterogeneity observed in SMA clinical manifestations. These insights have given rise to novel therapeutic strategies, including pharmacological interventions targeting epigenetic pathways and optimized management of environmental factors. Integrating multi-omics analyses holds promise for advancing personalized precision medicine approaches for SMA and potentially improving patient outcomes.